Identifying the Effects of Online Gaming Addiction on Students’ Academic Behavior in Biology Classes at SMA Negeri 5 Palu - Nikmah Nur Qoiriyah; Samsurizal `M. Suleman; Syech Zainal; Lilies; Moh. Sabran; Raya Agni (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aims to identify the impact of online game addiction on students’ academic behavior in Biology learning at SMA Negeri 5 Palu. A descriptive qualitative method was employed. The research subjects consisted of four Grade X Merdeka 2 students, selected purposively, and a Biology teacher. Data were collected through interviews and documentation. This study addresses a gap in previous literature by examining students’ subjective experiences regarding the effects of online game addiction on academic behavior in Biology classes at SMA Negeri 5 Palu. The findings indicate that online game addiction affects three aspects of students’ academic behavior: decreased classroom participation, lack of discipline in submitting assignments, and potential disruption of academic achievement. Among these aspects, students’ lack of discipline in completing assignments emerged as the most prominent and evident impact. This was supported by the consistency of interview responses from all informants, the normalization of rule violations, and confirmation from the Biology teacher that, without reminders, assignment submission could be delayed for up to one week. It can be concluded that interventions aimed at improving students’ discipline, time management, and daily limits on online gaming are needed through collaboration among schools, teachers, and parents.